The Effect of MaxiK Channel on Regulating the Activation of NLRP3 Inflammasome in Rats of Blast-induced Traumatic Brain Injury. (1st February 2022) - Ma, Jie; Wang, Junrui; Deng, Kaiwen; Gao, Yu; Xiao, Wenjing; Hou, Jun; Jiang, Changqing; Li, Jing; Yu, Botao
Highlights: The expression of MaxiK was elevated significantly in cerebral cortex of blast-induced traumatic brain injury (bTBI) rats. MaxiK might be involved in the process of neuroinflammation of bTBI. Paxilline could alleviate bTBI by blocking MaxiK channel and subsequently inhibition of NLRP3 inflammasome activation. Abstract: Abundant findings including our previous work proved that the NOD-like receptor family, pyrin domain-containing 3 (NLRP3) inflammasome exerts a key role in the process of neuroinflammation following blast-induced traumatic brain injury (bTBI). The opening of potassium channels leads to low K + environment in cells, which appears to be an essential requirement for NLRP3 inflammasome activation. Notably, MaxiK (BK) channel is significant for K + transport. The present study is aim to investigate the potential role of MaxiK in the activation of NLRP3 and to evaluate whether MaxiK channel blocker paxilline could confer beneficial effects on attenuating the severity of bTBI in rats. Rats were randomly assigned into five groups ( n = 8). MaxiK channel expression was measured in bTBI rats. The effect of paxilline on the expression of NLRP3 inflammasome, the level of inflammatory cytokines, brain injury biomarkers in serum and brain edema were also evaluated in bTBI rats. The results showed that the expression of MaxiK was elevated significantly in the cerebral cortex of bTBI rats. The treatment of MaxiK channel blocker paxilline suppressed the NLRP3 inflammasome expression substantially. In addition, paxilline could also decrease the level of pro-inflammatory cytokines and the biomarkers of brain injury and alleviate brain edema of bTBI rats. Our findings have revealed that MaxiK channel might be involved in the process of neuroinflammation of bTBI. Paxilline could depress neuro-inflammation response and alleviate brain injury by blocking MaxiK channel and subsequently inhibition of NLRP3 inflammasome activation.